Why do preferences for redistribution differ across countries? An experimental analysis - Gianluca Grimalda; Francesco Farina; Anna Conte; Ulrich Schmidt (Kiel Institute for the World Economy (IfW Kiel), 2023)
We test for different theories purporting to explain cross-country differences in income redistribution through standardized experimental choices. US Americans and Italians demand less redistribution than Norwegians and Germans, regardless of whether self-interest is relevant. Those earning (or expecting to earn) below-median incomes behave as "libertarians" more frequently in the US and Italy than in Germany and Norway. Above-the-median earners behave similarly across countries. Higher overconfidence by US Americans and Italians further reduces their demand for redistribution under uncertainty. The "Prospect of Upward Mobility" hypothesis holds similarly in all countries. US Americans do not reward individual merit more than others.
Keywords: C92; D63; H23; O57; 330; Income Redistribution; Inequality; Experiment; Merit; Overconfidence; Prospects of Upward Mobility; Cross-country research